Parents' Experience in an Italian NICU Implementing NIDCAP-Based Care: A Qualitative Study - Natascia Bertoncelli; Licia Lugli; Luca Bedetti; Laura Lucaccioni; Arianna Bianchini; Alessandra Boncompagni; Federica Cipolli; Anna Cinzia Cosimo; Giovanna Cuomo; Michela Di Giuseppe; Tamara Lelli; Veronica Muzzi; et al. (MDPI AG, 2022)
Background: The birth of a preterm infant and his/her immediate admittance to the Neonatal Intensive Care Unit (NICU) are sudden, unexpected, stressful and painful events for parents. In the last decade, in response to the increased awareness of the stressful experiences of parents, much attention has been paid to Family-Centered Care (FCC) and the implementation of the Newborn Individualized Developmental Care and Assessment Program (NIDCAP). According to the NIDCAP model, the infant-parents' dyad is the core of the care provided by the NICU professionals to reduce the stress experienced by parents. So far, the literature does not show a clear correlation between parental experiences and the NICU practices according NIDCAP principles. Aims: To explore how parents of preterm infants experienced the NIDCAP-based care from admission to discharge, in particular, their relationships with NICU professionals and with other parents, and the organization of the couple's daily activities during this process. Design: Qualitative exploratory study. Methods: Twelve parents of preterm infants born between January 2018 and December 2020 at the NICU of Modena, with a gestational age at birth of less than 30 weeks and/or a birth weight of less than 1250 g, were recruited. Three couples had twins, and the total number of infants was 15. All infants were followed for up to 24 months post-term age (PTA) for neurological outcomes. Each couple was given a semi-structured online interview about their experience during their infant's hospitalization in the NICU up to discharge. The interview was developed around three time points: birth, hospitalization and discharge. The data analysis was conducted according to the template analysis method. Results: The admission to the NICU was unexpected and extraordinary, and its impact was contained by the skilled staff who were capable of welcoming the parents and making them feel they were involved and active collaborators in the care of their infant. The emotional experience was compared to being in a blender; they were overwhelmed by changing emotions, ranging from terrible fear to extreme joy. The couple's activities of daily life were reorganized after the infant's birth and admission to the NICU. Fathers felt unbalanced and alone in taking care of their partners and their children. Conclusions: This is the first study in Italy to explore parental experience in an NICU implementing NIDCAP-based care. The NIDCAP approach in the NICU of Modena helps parents to be involved early, to develop parental skills, and to be prepared for the transition home; and it also facilitates and enhances the relationship between parents and NICU staff.